Spectrophotometric Determination of Bromhexine Hydrochloride by Azo-Dye Formation Reaction - Nabeel Othman; Shilan Omer (مجلة التربية والعلم, 2009)
ABSTRACT A spectrophotometric method for the assay of trace amounts of bromhexine-HCl based on the reaction of bromhexine-HCl with nitrite ion to form the corresponding diazonium salt followed by coupling reaction with pyrogallol in a acidic medium to form a stable and a soluble yellow azo dye with maximum absorption at 387 nm. Beer’s law is obeyed in the concentration range of 20-280g of bromhexine-HCl in a final volume of 25 ml (0.8- 11.2 ppm) with a molar absorptivity of 1.031104 L.mol-1.cm-1, a relative error of -0.36 to +0.72 % and a relative standard deviation of 1.07 to 1.72 %, depending on the concentration level of bromhexine-HCl. The method has been successfully applied for the assay of bromhexine-HCl in various pharmaceutical preparations.